Financial Literacy Among Adults: A Methodology Review and Systematic Review with VOS Viewer Application - Asteria, Beta; Kurnianto Tjahjono, Heru (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2025)
This research aims to test research with the theme of Financial Literacy methodologically and systematically. The methodology research results show that setting the number of samples. The sample technique chosen greatly determines the success of the research. Incorrect sampling produces suboptimal results and cannot be population-specific. The sample selection technique is random or not influenced by the time required to collect data and regulates the logical sample required by the researcher. For example, regional sampling. The research results are based on a systematic review of Scopus journal data; journals searched that meet the journal search requirements with the keywords Literacy, financial, and Young. Journal entry limits with the subject "Business Management and Accounting Journal", journals in English from 2015 to 2024.54 journals that meet the requirements.7 clusters related to the topic of Financial Literacy in young adults. The clusters are detailed as follows: Cluster 1 (5 Items) are bodega, convenience store, financial inclusion, informal business practices, informal female entrepreneurship; Cluster 2 (5 items): financial attitude, financial awareness, financial knowledge, first-year student, literature review; Cluster 3 (5 items) are attitude toward money, financial behavior, financial literacy, financial planning action, Seci Strategy; Cluster 4 (3 items) are Financial behavior, financial socialization, financial well-being; Cluster 5 (3 items) are Interest in business, Level of financial literacy, Questionaire; Cluster 6 (3 items)are Financial Educations, Financial Fragility, Student load debt; and Cluster 7 (2 items) are Commercial literacy and small business. Then the results of the VOS Viewer also show that the research on Financial Literacy will only be carried out in 2023, and in 2024, most research will be carried out on this theme.